Factors affecting purchasing decision of houses in the urban residential property market in Klang Valley, Malaysia - Paul Anthony Mariadas; Hussin Abdullah; Norehan Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
Property expansion can be considered as one of the essential activities that drive out the stability and enhances human being lifestyle. The overall evaluation of housing as a kind of investment product displays housing accounts for a large proportion of the average income in a mankind productive life. Housing investment is considered long term investment because it is the main point affecting the living standard of people from both macro and micro perspectives. Thus, the objective of this study is to determine the urban residential purchase decision in Klang Valley, Malaysia. Factors such as finance, location, neighbourhood, and structural attributes were investigated. Data was collected using a probabilistic sampling method, particularly a stratified random sampling technique. The descriptive approach, correlation, and multiple regression analysis are used to analyse the data. This research found three factors that influenced the urban residential property purchase decision in Klang Valley, Malaysia, which are finance, location and structural. By understanding the motivation behind purchasing their first home, investors would be able to gauge the factors that matter most before investing in the urban property market.